TRADISI SABUNG AYAM DI KABUPATEN TANA TORAJA PERSPEKTIF SIYASAH SYAR’IYYAH - Fatimah, Fatimah; Nurnaningsih, Nurnaningsih (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar’iyyah, 2020)
This study aims to describe the Implementation of Law No. 7/1974 on the Cockfighting Tradition in Tana Toraja Regency and the benefits and Strengthening of the Cockfighting Tradition in Tana Toraja District which have no legal implications. This research uses descriptive qualitative research methods (field research). The results of this study indicate that Law Number 7 of 1974 concerning Control of Gambling has not been effectively applied in Tana Toraja Regency due to people who are not aware of the law. One of the benefits of the tradition of cockfighting in Tana Toraja Regency is helping families who carry out funeral rites (Rambu Solo ’) through community contributions that come to watch cockfighting, strengthening the tradition of cockfighting that has no legal implication is through efforts to tackle crime one of which is to provide counseling to the community believes that cockfighting is an unlawful act, because a cockfight carried out now is no longer the same as a cockfight committed by the ancestors of the community first.